The Role of Musyrif in Establishing Morality at The Darul Ilmi Muhammadiyah Tarakan Islamic Boarding School - Hamin, Abdul; Bustam, Betty Mauli Rosa (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
Morals are the most important thing and must be owned by all santri, so the role of musyrif is needed in shaping the morals of students because musyrif is the spearhead of Islamic boarding schools and is required to guide the morals of students while at the Darul Ilmi Muhammadiyah Islamic Boarding School. This study aims to determine the role of musyrif in shaping the morals of students who are naughty or often commit violations so that these students can be morally formed without physical violence, provide a deterrent effect on students so they do not repeat it again, and create a harmonious atmosphere between students and musyrif. The method used in this research is qualitative. Data obtained through journals, interviews, and documentation. The data collection technique used is descriptive analysis. As for the results of research that can be carried out by Musyrif when dealing with naughty students by handling a heart-to-heart approach.